CURRENT SITUATION AND PROSPECTS OF PRODUCTION AND RESERVES OF PERMANENT MAGNETS OF RARE EARTHS: BRAZIL × WORLD - Franciele Weschenfelder; Philippe Pauletti; Sérgio Deitos Bittencourt; Leandro Pelegrini; Diogo Kaoru Ito; Lirio Schaeffer (Tecnologia em Metalurgia, Materiais e Mineração, 2012)
Generating energy from renewable sources is not an easy task since it requires different types of technologies, which can add much cost to the system. For this reason, investment in research in this area can be an alternative for economic feasibility of wind power plants, for example. One line of research in this area is the study of new materials such as permanent magnets, with even better properties. These magnets, when used in wind generators add many advantages in the operation there of, and a high torque/volume. For this application it is necessary that these magnets have high coercive field (Hc) and high remanent induction (Br). Brazil still has no competition in the industry of permanent magnets, so many studies by government and private enterprise are under development in the country. There is a special focus to the Rare Earths Magnets, the primary raw material for production of permanent magnets.